Sistema de gestão integrado de qualidade e ambiental para implantação de equipamentos facilitadores em cavernas turísticas - LEVENHAGEN, BLANCHE SOUSA (2019)
This research deals with the analysis of the technical document called the Conceptual Project for Facilitating Equipment in Caves (CP). The CP was an unfolding of the Speleological Management Plans (SMP), whose objective was to establish procedures for the installation of facilitation equipment (bridges, stairs, walkways, etc.). The objective of this research was to identify the gaps that could impede the application of the CP and thus interrupt the process of implementation of SMP. Based on the analysis of the PC and the SMP, this research resulted in a change in the design of the CP construction and, from this, the construction of an Integrated Management System for the Implementation of Facilitating Equipment in Tourist Caves in Conservation Units (IMS-IFE). The IMS-IFE consolidated, in a format similar to that recommended in the technical standards ABNT ISO 9001 and 14001, the new CP design based on adaptive management. The IMS-IFE is an unprecedented product for the management of tourist caves, with potential to influence public policies for the management of tourist caves in conservation units from the point of view of quality and environmental management systems.